Electrophysiological and other aspects of the relaxant action of isoprenaline in guinea-pig isolated trachealis. - Allen, S. L. (1985)
In guinea-pig isolated trachealis isoprenaline (0.001-0.1 mumol l-1) caused concentration-dependent relaxation. Propranolol (1 mumol l-1) antagonized the effects of isoprenaline by more than 100 fold but did not modify the relaxant action of sodium nitrite. The tracheal relaxant actions of isoprenaline and ATP were unaffected by apamin (0.1 mumol l-1) but apamin profoundly antagonized the effects of noradrenaline and ATP on guinea-pig isolated taenia caeci. Tetraethylammonium (TEA; 8 mmol l-1) and procaine (5 mmol l-1) each evoked tracheal spasm but neither agent antagonized the isoprenaline-evoked relaxation of the trachealis. Trachealis exposed to K+-rich (120 mmol l-1) Krebs solution developed near-maximal tension. Both isoprenaline and sodium nitrite relaxed the K+-depolarized tissue though concentration-effect curves for both relaxants were moved to the right compared to those obtained in non-depolarized tissues. The maximal effect of sodium nitrite was markedly reduced. Intracellular electrophysiological recording showed that isoprenaline (0.01-1 mumol l-1) caused hyperpolarization and reduced or abolished slow wave discharge in trachealis muscle. These effects were accompanied by relaxation. Propranolol (1 mumol l-1) virtually abolished both the electrical and mechanical responses to isoprenaline (0.1 mumol l-1). Apamin (0.1 mumol l-1) did not alter the spontaneous electrical activity of trachealis cells or their electrical and mechanical responses to isoprenaline (0.1 mumol l-1). TEA (8 mmol l-1) caused depolarization and often increased slow wave amplitude and induced spike discharge. Isoprenaline (0.01 mumol l-1) failed to hyperpolarize TEA-treated trachealis cells. Higher concentrations of isoprenaline suppressed TEA-induced spasm, caused hyperpolarization and thereby increased slow wave or spike amplitude. Slow wave or spike frequency decreased as the hyperpolarization progressed but abolition of slow waves or spikes sometimes required more than 4 min exposure to isoprenaline. Procaine (5 mmol l-1) increased the amplitude of slow waves and induced spike discharge. Procaine markedly reduced the hyperpolarization induced by isoprenaline (0.1 and 1 mumol l-1) but had little effect on isoprenaline-induced relaxation. It is concluded that isoprenaline activates beta-adrenoceptors in guinea-pig trachealis and thereby evokes relaxation and hyperpolarization of the smooth muscle. The hyperpolarization does not involve the opening of apamin-sensitive K+-channels and it probably plays a supportive rather than a crucial role in the process by which isoprenaline-induced relaxation is achieved.